Emotional uneasiness perceived by parents of children with specific language impairment - ROMANÒ, MANOLA; BURELLI, ALESSANDRA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2006)
In children with specific language impairment (SLI) the emotional uneasiness is a correlated problem that is manifested when these subjects are in contact with their equals who have not this kind of language problem. This research analysis on emotional uneasiness was estimated by their parents’ perception of them, using the CBCL/ 4-18 Children Behavior Checklist/4-18 scale of Achenbach. The study was carried out on Italian pre-school age and primary school children with SLI and we show the symptoms, intensity and frequency of emotional uneasiness in relation to children of the same age without language impairments. The results underline that emotional uneasiness is present in children with SLI and how their parents perceive it. There are some qualitative and quantitative differences between perception of symptoms in mothers and fathers, although both parents notice attention deficit problems in their SLI children.